Automation and income inequality in Europe - Karina Doorley; Jan Gromadzki; Piotr Lewandowski; Dora Tuda; Philippe Van Kerm (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
We study the effects of robot penetration on household income inequality in 14 European countries between 2006-2018, a period of rapid adoption of industrial robots. Automation reduced relative hourly wages and employment of more exposed demographic groups, similarly to the results for the US. Using robot-driven wage and employment shocks as input to the EUROMOD microsimulation model, we find that automation had minor effects on income inequality. Household labour income diversification and tax and welfare policies largely absorbed labour market shocks caused by automation. Transfers played a key role in cushioning the transmission of these shocks to household incomes. – – Wir untersuchen die Auswirkungen der Roboterdurchdringung auf die Ungleichheit der Haushaltseinkommen in 14 europäischen Ländern zwischen 2006 und 2018, einer Zeit der schnellen Einführung von Industrierobotern. Ähnlich wie in den USA hat die Automatisierung die relativen Stundenlöhne und die Beschäftigung von stärker belasteten demografischen Gruppen reduziert. Unter Verwendung von roboterbedingten Lohn- und Beschäftigungsschocks als Input für das Mikrosimulationsmodell EUROMOD finden wir, dass die Automatisierung nur geringe Auswirkungen auf die Einkommensungleichheit hatte. Die Diversifizierung des Arbeitseinkommens der Haushalte und Steuer- und Sozialpolitik fingen die durch die Automatisierung verursachten Arbeitsmarktschocks weitgehend ab. Transfers spielten eine Schlüsselrolle bei der Abfederung der Übertragung dieser Schocks auf die Haushaltseinkommen.
Keywords: J24; O33; J23; 330; Robots; automation; tasks; income inequality; wage inequality; microsimulation